Mistaken gifts after Pitt v Holt - Hacker, B (Oxford University Press, 2014)
In Pitt v Holt [2013] UKSC 26, the Supreme Court ruled on the conditions under which a voluntary deed can be set aside for spontaneous mistake. This article explores the ramifications of the decision for the law of mistaken gifts more generally. It examines the suggestion that Pitt v Holt establishes (or confirms the existence of) a special restitutionary regime for all gift transactions, as well as the alternative interpretation which regards Pitt v Holt as concerning only the equitable remedy of rescission, leaving common law claims unaffected. Drawing on the experience of other legal systems, the article argues that English law should not develop a special law of gifts nor cement the historical dividing line between common law and equity, but should instead use Pitt v Holt as a trigger and catalyst for rationalizing the evolving ordinary law of unjust enrichment.